World-systems analysis: toward a new epistemology - Umruk, Okan (My University, 2005)
Dünya-sistemleri analizi aşağı yukarı otuz yıldan bu yana akademik literatürün gündemindedir. Dünya-sistemleri analizinin çarpıcı bir etkiye sahip olduğu genel olarak kabul edilmiştir. Bir anlamda, modern sosyal bilim epistemolojisini doğrudan hedeflemiş ve onun yapıbozumunu önermiştir. Temelde bilimsel soyutlamanın daha kapsamlı olanaklarını aramıştır. Dünya-sistemleri analistlerinin amacı, sistem/ tarih, nitelik/ nicelik gibi karşıtlıklar içindeki metodolojik hiyerarşileri ortadan kaldırma temelinde, kavramsallaştırmanın uygun araçlarını keşfetmekti. Onlara göre, bilimcilerin araştırılanın en kapsamlı ve en açıklayıcı bilimsel soyutlamasına yakınsamalarını sağlayan bu türden bir epistemolojik tercih, somutun bütünsel kavrayışının tek uygun yöntemiydi. Yapmaya çalıştıkları, modern sosyal bilimin epistemolojisine karşı açık bir epistemolojik meydan okuma anlamına geliyordu. Bu tez, dünya-sistemleri analizinin varsayımlarını desteklemek üzere yazılmıştır. Tezin yazarı dünya-sistemleri analizinin varsayımlarının yeni bir epistemolojiye doğru atılan büyük bir adım olduğuna inanmaktadır. Dünya-sistemleri analizine karşı alternatif bir perspektif olarak tasarlanmış olan dünya sistemi kuramının varsayımları, bu çalışmanın yazarı tarafından egemen epistemolojinin dünya-sistemleri analizine yönelttiği dikkate değer bir yanıt olarak görüldüğü için bu tezde geniş olarak ele alınmıştır. Tezin yazarı, bu çalışmanın varolan epistemolojik tartışmaya anlamlı bir katkı sunması umudunu taşımaktadır. World-systems analysis has been on the agenda of the academic literature for some thirty years. It is widely accepted that the impact of world-systems analysis was striking. In a sense, it directly aimed at the epistemology of modern social science and offered a deconstruction of it. It basically searched for more comprehensive resources of scientific abstraction. The aim of the world-systems analysts was to find out proper ways of conceptualization on the basis of abolishing methodological hierarchies within the binary oppositions such as system/ history, quality/ quantity. They argued that such an epistemological preference, that would enable scientists to converge to the most comprehensive and explanatory way of scientific abstraction of what is to be researched, was the only appropriate method to reach the holistic comprehension of the concrete. What they were trying to do was tantamount to a certain epistemological challenge against the epistemology of modern social science. This thesis has been written to support the assumptions of world-systems analysis. Writer of the thesis believes that the assumptions of world-systems analysis is a great step toward a new epistemology. World system theory, which was devised as an alternative perspective to world-systems analysis, has been widely taken up in the thesis on the grounds that the assumptions of world system theory has been acknowledged by the writer of this study as a remarkable response of the prevailing epistemology to world-systems analysis. Writer of the thesis hopes that this study forms a purposeful contribution to the existing epistemological debate.
Keywords: Epistemoloji; Epistemoloji (Bilgi kuramı); Felsefe